Solid intracystic papillary carcinoma in male breast: case report - Geron, Vanessa; Queiroz, Evelyn Borges; Lopes, Fernanda Santos; Dair, Elisabete Lilian; Carloni, Marcelo Ballaben (Mastology, 2021)
The intracystic papillary carcinoma (IPC) is one of the rarest types of breast cancer, mainly in men, representing less than 1% of the malignant diseases in the male sex. It is frequently associated with the ductal carcinoma in situ (DCIS), but there are also other forms such as the pure and the invasive ones. The male population breast cancer diagnosis is late and, therefore, it has a worse prognosis. The diagnosis is given by imaging tests and anatomopathological studies. The treatment consists of excisional tumor therapy, which can be carried out conservatively or through mastectomy, with or without adjuvant therapy.